ANALISIS KEMAMPUAN KOMUNIKASI MATEMATIS SISWA SMP TERHADAP SOAL-SOAL BANGUN RUANG SISI DATAR - Nurlaila, Siti; Sariningsih, Ratna; Maya, Rippi (IKIP Siliwangi, 2018)
This research is to find out the mathematical communication skills of VIII junior high school students about building a flat side space. This research method is a qualitative descriptive study. The subject of this research is 18 students in one junior high school in Bandung regency. The test instrument used is a description form. The indicator used in this study there are 5 indicators of mathematical communication ability, namely expressing ideas, situations and relations with images, expressing mathematical situations or everyday events into mathematical models, explaining and making questions of mathematical problems, low indicators only obtain an average percentage averaged 12%, based on the results of calculations using the Microsoft Exel application the overall student communication skills of these five indicators are still low below 50% which is only 44%.